2018
DOI: 10.18632/oncotarget.25755
|View full text |Cite|
|
Sign up to set email alerts
|

The nuclear-cytoplasmic trafficking of a chromatin-modifying and remodelling protein (KMT2C), in osteosarcoma

Abstract: Osteosarcoma is the most common paediatric primary non-hematopoietic bone tumor; the survival is related to the response to chemotherapy and development of metastases. KMT2C is a chromatin-modifying and remodelling protein and its expression has never been studied in osteosarcoma. The aim of this study was to understand the role of KMT2C in the osteosarcoma carcinogenesis and metastatic progression to identify a new molecular target and to provide new therapeutic approach.We performed the immunohistochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A preliminary screen identified 17 nonsynonymous SNVs located on 15 genes, some of which were previously found to be related to osteosarcoma prognosis, such as KMT2C, PALB2, and FGFR4. ( 34‐37 ) Our model demonstrated that polymorphisms on these genes contributed to the different response to chemotherapy, suggesting the potential of gene variants for improving the understanding of tumorigenic mechanisms and predicting disease outcomes. Notably, our results are partly consistent with that the therapeutic response may be influenced by the patients' age; ( 38,39 ) these 17 nonsynonymous SNVs are suggested to be more effective in distinguishing the prognosis of adults.…”
Section: Discussionmentioning
confidence: 86%
“…A preliminary screen identified 17 nonsynonymous SNVs located on 15 genes, some of which were previously found to be related to osteosarcoma prognosis, such as KMT2C, PALB2, and FGFR4. ( 34‐37 ) Our model demonstrated that polymorphisms on these genes contributed to the different response to chemotherapy, suggesting the potential of gene variants for improving the understanding of tumorigenic mechanisms and predicting disease outcomes. Notably, our results are partly consistent with that the therapeutic response may be influenced by the patients' age; ( 38,39 ) these 17 nonsynonymous SNVs are suggested to be more effective in distinguishing the prognosis of adults.…”
Section: Discussionmentioning
confidence: 86%
“…Further, the gene KMT2C , which is mutated in 67% of all OS samples, involved in OS carcinogenesis and progression [ 61 ]. Similar to results of our study, the exome analysis shows a high load of somatic variations in KMT2C , which can have histone modification-related activity in OS [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that miR-93-5p is closely related to tumorigenesis [ 18 ]. The KMT2C gene has mutations or deletions in many tumors, including leukemia, liver cancer, pancreatic cancer, gastric cancer, cholangiocarcinoma, ovarian cancer, and bladder transitional cell carcinoma [ 19 , 20 ]. In recent years, several studies have found that lncRNAs may play a biological role by regulating downstream target genes through miRNA adsorption processes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%